(3ebGdI aj Cf GdcQI ChSY GdCTcGd GdeLSeIs - (3GHf GdgjKe , eMeO Hf GdMSf Hf GdgjKe, CHh Ydj HWdjehS GdKGfj,J (B430 (3g` s
(3ChdgG (B:s
(3bhd GdMSf Hf GdgjKe ai Gf GdcQI GhSY GdCTcGd GdeLSeI GdJi GMGWGJgG eJSGhjI hGf GdOGFQI GhSY GdCTcGd GdeSWMI s
(3BNQgG (B:s
(3hEf eG cGf CbQH Edi GdGSJOGQI ef gPg GdCTcGd cGf GhSY eeG jYO efgG hPdc eG bUOfG dJHjjfg ai gPg GdebGdI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B83 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B225s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(5/3934) s
Keywords: (3GdQjGVjGJs